Answer:
x = ± 4
y = - 2
Step-by-step explanation:
y = 0.5x² - 10 ------------------------(I)
y = -x² + 14 ------------------------(II)
Substitute the y value in equation (II)
0.5x² - 10 = -x² + 14 {Add x² to both sides}
0.5x² + x² -10 = 14 {combine like terms}
1.5x² - 10 = 14 {Add 10 to both sides}
1.5x² = 14 + 10
1.5x² = 24 {Divide both sides by 1.5}
1.5x²/1.5 = 24/1.5
x² = 16
x = ±4
Substitute x = 4 in (I)
y = 0.5 * 4² - 10
= 0.5*16 - 10
= 8- 10
y = -2
Substitute x = -4 in (I)
y = 0.5 * (-4)² - 10
= 0.5*16 - 10
= 8- 10
y = -2
Expanding
-3h-15+2=4h+24-9
-3h-4h=24-9-2+15
-7h=28
h=4
Answer:
y=3/4 x-6
Step-by-step explanation:
i passed this
Answer:
9m, 12m, 15m
Step-by-step explanation: